Research and Application Analysis of Heart Rate Monitoring Technology Based on CSI - Ou , Xingtong (Transactions on Computer Science and Intelligent Systems Research, 2025)
Chronic diseases affecting younger people have become prevalent in contemporary society. Among chronic diseases, cardiovascular and cerebrovascular diseases are predominant, with countless people dying from cardiovascular diseases each year. Long-term heart rate variability (HRV) monitoring can warn of arrhythmia, myocardial ischemia, and other conditions, reducing the mortality rate from acute events by 30%. The advent of non-contact detection technology has made long-term monitoring possible. This paper reviews heart rate monitoring technologies based on channel state information (CSI), discusses techniques such as CSI phase difference, rotation projection, and discrete wavelet transform, and examines their current applications in medical and other fields, to provide new technical insights for cardiovascular health management. It also points out that existing technologies generally suffer from high computational complexity and susceptibility to complex environmental influences. In the future, we hope to combine intelligent technology to enhance environmental adaptability and quickly realize the transition of CSI heart rate monitoring from clinical applications to full-scene applications.